2010
DOI: 10.1002/jgm.1514
|View full text |Cite
|
Sign up to set email alerts
|

Gene knockdown with lentiviral vector‐mediated intrathecal RNA interference of protein kinase C gamma reverses chronic morphine tolerance in rats

Abstract: A single injection of LV-shPKCγ reversed MT by reducing the expression of PKCγ in the spinal cord. These findings indicate that the use of LV-shPKCγ might be a potential strategy for therapy in MT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…without using viral vectors (29), to provide gene knockdown or gene silencing using shRNA or siRNA (30,31), as well as in regeneration strategies using neural precursor cells (32). However, none of those previous studies focused specifically on myelinating Schwann cells, because ubiquitous promoters were used.…”
Section: Discussionmentioning
confidence: 99%
“…without using viral vectors (29), to provide gene knockdown or gene silencing using shRNA or siRNA (30,31), as well as in regeneration strategies using neural precursor cells (32). However, none of those previous studies focused specifically on myelinating Schwann cells, because ubiquitous promoters were used.…”
Section: Discussionmentioning
confidence: 99%
“…To induce morphine tolerance, 10 μg morphine sulfate (in a volume of 10 μL) was delivered via an intrathecal catheter twice daily for 7 d. The control group was injected with 10 μL normal saline. Injections were followed by administration of 10 μL normal saline to flush the catheter [52]. Morphine analgesia was assessed on the test day using the tail-flick test both before and 30 min after morphine administration.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a variety of approaches have been explored to elucidate the potential role of PKCγ as a pain mediator in nociceptive signal transduction [26-29]. It has been demonstrated that PKCγ is involved in many aspects of cellular sensitization, including modulation of channel conductivity, increased trafficking of receptors, and release of excitatory neurotransmitters [30].…”
Section: Introductionmentioning
confidence: 99%